MRI brain tumor segmentation: A forthright image processing approach - Noor Elaiza Abd Khalid; Muhammad Firdaus Ismail; Muhammad Azri AB Manaf; Ahmad Firdaus Ahmad Fadzil; Shafaf Ibrahim (Bulletin of Electrical Engineering and Informatics, 2020)
Brain tumor is a collection of cells that grow in an abnormal and uncontrollable way. It may affect the regular function of the brain since it grows inside the skull region. As a brain tumor can be possibly led to cancer, early detection in Computed Tomography (CT) or Magnetic Resonance Imaging (MRI) scanned images are crucial. Thus, this paper proposed a forthright image processing approach towards detection and localization of brain tumor region The approach consists of a few stages such as pre-processing, edge detection and segmentation. The pre-processing stage converts the original image into a greyscale image, and noise removal if necessary. Next, the image is enhanced using image enhancement techniques. It is then followed by edge detection using Sobel and Canny algorithms. Finally, the segmentation is applied to highlight the tumor with morphological operations towards the affected region in the MRI images. The in-depth analysis is measured using a confusion matrix. From the results, it signifies that the proposed approach is capable to provide decent segmentation of brain tumor from various MRI brain images.